Identification and classification of evaluation indicators for scientific and technical publications and related factors - Hassan Mahmoudi Topkanlo; Mehrdad CheshmehSohrabi (Information Research: An International Electronic Journal)
Introduction. Given the importance of the issue of the widespread impact of scientific and technical publications in today's world, and the diversity and multiplicity of indicators for measuring these publications, it is a necessity to classify these indicators from different angles and through different tools and methods.